Effects of Storytelling on Improving EFL Students’ Critical Thinking and Reading Comprehension - Sahibzada, Javed; Ahmadzai, Yar Mohammad Bahrami; Niaz, Azadkhan; Laftah, Susan Hussein (American International Journal of Social Science Research, 2020)
The purpose of this study is to find the effects of storytelling (ST) on improving critical thinking and reading comprehension of EFL students at Kandahar University. The design of the study was quasi-experimental with critical thinking and reading comprehension pre and posttests. Total 27 Afghan EFL students were selected based on their performance on Placement test. The participants of experimental group listened to their teacher telling the story. In order to find the improvement and different between these variables is significant the Paired Sample T-Test was administrated and the result indicates that there is significant improvement in post-tests in areas of reading comprehension and critical thinking in group of storytelling. However, improvement is higher in reading comprehension section than critical thinking.